Pulmonary Embolism Mimicking Other Diseases: Diagnostic Pitfalls and Atypical Clinical Presentations - Koladzyn, John; Margielewska, Weronika; Słodyczka, Anna; Siemaszko, Kai; Badran, Mahmoud; Wasilewski , Luiza; Twombly, Gregory; Jankowski , Gabriela; Jankowski, Marianna (Journal of Education, Health and Sport, 2026)
Background: Pulmonary embolism (PE) remains a clinically significant and potentially fatal condition whose diagnosis may be difficult because its manifestations often overlap with more common cardiopulmonary, abdominal, and neurological disorders. In addition to classic presentations, PE may resemble acute coronary syndrome, heart failure, pneumonia, syncope, abdominal pathology, or neurological disease, which may contribute to delayed recognition. Material and methods: This manuscript was prepared as a narrative literature review based on selected publications addressing clinical variability, diagnostic pathways, disease mimicry, laboratory and imaging limitations, cognitive bias, and strategies to improve diagnostic accuracy in PE. The reviewed literature included observational studies, validation studies, systematic reviews, meta-analyses, guideline documents, and illustrative case reports. Results: The reviewed literature suggests that PE may present across a broad and often misleading clinical spectrum. Diagnostic difficulty appears to arise from nonspecific symptoms, overlap with alternative diagnoses, imperfect performance of clinical prediction rules, limited specificity of biomarkers, interpretive limitations of electrocardiography, and technical or contextual limitations of imaging. Cognitive biases may further contribute to diagnostic delay or initial misclassification. Evidence also suggests that probability-adjusted diagnostic approaches and careful integration of clinical assessment with imaging findings may improve diagnostic accuracy. Conclusions: PE may mimic a wide range of other conditions and may remain unrecognized when early findings are nonspecific or misleading. A structured diagnostic approach combined with sustained clinical suspicion may help reduce missed or delayed diagnosis, particularly in patients with atypical presentations.